TALASEMIA BETA HEMOGLOBIN E (Hemoglobin E Beta Thalassemia) - Viviyanti Zainuddin; Agus Alim Abdullah; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Thalassemia is a quantitative abnormality of the hemoglobin marked by inadequate hemoglobin synthesis due to the lack orabsence of synthesis of one or more globin polypeptide chains. Hemoglobin variant is a qualitative abnormality due to the presence ofthe abnormal amino acid sequence of one or more globin polypeptide chains. HbE β thalassemia is a disorder of hemoglobin that resultsfrom the fusion between the gene β-thalassemia allele from one parent with a gene HbE allele from another parent. In this case, HbEβ-Thalassemia patient was a 4.8 year girl diagnosed with hemoglobin E-beta thalassemia based on history and clinical manifestations;pale, the presence of splenomegaly and hepatomegaly. Laboratory tests were Hb: 7.7 g/dL, MCV: 52.9 fl, MCH: 17.7 pg, MCHC: 33.5g/dL and ferritin: 1012 ng/mL. Peripheral blood smear evaluation showed a microcytic hypochromic anemia with hemolytic signs andinfected features of leukocytes. Hb electrophoresis using HPLC showed a Hb F: 37.7% and HbA2 52.4%, indicating that HbA2 was falsehigh due to coeluating with HbE. The patient was treated by blood transfusion and received additional therapy such as folic acid, ironchelation and vitamin E.